1997
DOI: 10.1093/hmg/6.11.1961
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the SMN Gene, the Spinal Muscular Atrophy Determining Gene, in the Mammalian Central Nervous System

Abstract: The survival motor neuron (SMN) gene is the putative disease gene for human spinal muscular atrophy (SMA), an autosomal recessive disorder characterized by progressive degeneration of lower motor neurons. Two copies of the gene, centromeric and telomeric, are present in the same 5q13 chromosomal region in humans. However, only the telomeric gene is affected in SMA. The SMN gene(s) encode(s) a novel protein of unknown function. To gain insights into the role of SMN in neurons, we have identified the SMN gene or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
105
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 27 publications
16
105
1
2
Order By: Relevance
“…3 Other species including mouse and rat only have the homologue of the telomeric copy of SMN. 4,5 The two SMN genes and their predicted proteins are identical except for a few translationally silent nucleotides within exon and intron sequences. The SMN1 copy is deleted or gene converted in more than 95% of SMA patients, 3,6 while mutations in SMN2 have no clinical consequence.…”
Section: Introductionmentioning
confidence: 99%
“…3 Other species including mouse and rat only have the homologue of the telomeric copy of SMN. 4,5 The two SMN genes and their predicted proteins are identical except for a few translationally silent nucleotides within exon and intron sequences. The SMN1 copy is deleted or gene converted in more than 95% of SMA patients, 3,6 while mutations in SMN2 have no clinical consequence.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, the two genes generate different proportions of alternatively spliced isoforms: about 90% of transcripts from the SMNt gene are full length, whilst the SMNc gene produces predominantly transcripts which lack exon 7 and, to a less amount, transcripts that lack exon 5 or both exons 5 and 7 as well as full length transcripts. 6,18 Both SMNt and SMNc are expressed in most if not all tissues; 6,[19][20][21] (own unpublished data 1996). Immunocytochemical studies of HeLa cells using monoclonal antibodies against SMN have shown that the protein is localised in both the cytoplasm and in the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…So far, we know that SMN is ubiquitous, conserved across species, highly expressed during early development, and that SMN levels are higher in spinal cord and brain, but significantly down-regulated after birth [Battaglia et al, 1997; La Bella et al, 1998;Williams et al, 1999]. The SMN protein is one member of a large, highly stable macromolecular complex that localizes in both the nuclear and cytoplasmic compartments of a cell [Liu and Dreyfuss, 1996].…”
Section: Smn: How Many Functions Can a Single Protein Possess?mentioning
confidence: 99%
“…The SMN protein is subject to both temporal and spatial regulation: the highest SMN levels have been reported in brain, spinal cord, kidney and heart [Lefebvre et al, 1997;Coovert et al, 1997;Burlet et al, 1998] and SMN is especially abundant throughout embryonic development [Battaglia et al, 1997;Burlet et al, 1998; La Bella et al, 1998]. The levels of SMN protein diminish during the early postnatal period; however, the timing of this repression varies among tissues [Kernochan et al, 2005].…”
Section: Are Smn1 and Smn2 As Identical As They Appear To Be?mentioning
confidence: 99%